Necessity and Implementation of BlockChain Technology - Mir, Waseem Akram (International Journal of Scientific Research and Management (IJSRM), 2017)
Transactions between individuals have always been a part and parcel of human society for the division of labour made people interdependent. The medium of transaction has also been evolving along with the evolution of society and human consciousness from barter system to commodity money to fiat currency and now to digital currency or cryptocurrency. But since evolution is a form of error correction, the problem of double spending in digital currency was solved by a distributed ledger system called Blockchain. Since 2008 onwards the blockchain technology has been separated from bitcoins to be injected to many other problems related especially to banking transactions. Blockchain technology enables the creation of decentralized currencies, smart contracts and intelligent assets that can be controlled over the Internet